The possibilty of the combined heat and power (CHP) usage at Sampadi Palm Oil processing plant - Jaafar, Fatimah (Universiti Malaysia Sarawak (UNIMAS), 2001)
Combined Heat and Power (CHP) is a generation of electrical and thermal energy in a single process. In simple words, it could be explained as making electricity and use the rejected heat to fill the thermal requirement. The heat, which is normally lost in the production one form of energy, will be recovered to generate another form of energy. The making use of this waste heat differentiates CHP from conventional electric power generation. Sampadi Palm Mill, Lundu Sarawak is a self-sufficient industry as far as energy utilization is concerned. It is equipped with steam turbine, boiler and diesel engine. They used palm fruit waste as a boiler fuel. Through observation, there is no heat exchanger use to convert the heat to useful purpose. Therefore, this study is done to examine whether Sampadi Palm Mill is possible to utilize CHP or not. The analysis involve in this study are boiler analysis, thermal efficiency, steam turbine analysis and load factor analysis. The boiler analysis, thermal efficiency and steam turbine analysis are used to measure the capability of the existing steam turbine and boiler system. Meanwhile, the electric and thermal load factor analysis is used to indicate the possibility of CHP at Sampadi Palm Mill. The finding of lower electric and thermal load factor, which is 2.51 % and 1.96% respectively shows that Sampadi Palm Mill is not a good candidate for CHP.